2014
DOI: 10.1080/09168451.2014.936346
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of characteristic floral scent compounds in Prunus mume and related species

Abstract: In order to investigate the difference in their characteristic floral scents between Prunus mume Siebold & Zucc. and the related Prunus species, their headspace volatiles and endogenous extraction were analyzed by gas chromatography–mass spectrometry. The efficiency of substrate utilization of the flowers was studied by incubating them with different alcohol substrates. Our results indicated that benzyl acetate is a dominant compound influencing the characteristic floral scent of P. mume. An alcohol substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…In earlier research, we found that the dominant compound responsible for the fragrance of P. mume flowers was ester benzyl acetate 25 , which is synthesized by the benzenoid/phenylpropanoid pathway. CbBEAT in C. breweri has been reported to catalyze the synthesis of benzyl acetate using benzyl alcohol and acetyl-CoA as substrates, and the substrate benzyl alcohol has been shown to be synthesized from the reduction of benzaldehyde in plants 2,10 .…”
Section: Resultsmentioning
confidence: 99%
“…In earlier research, we found that the dominant compound responsible for the fragrance of P. mume flowers was ester benzyl acetate 25 , which is synthesized by the benzenoid/phenylpropanoid pathway. CbBEAT in C. breweri has been reported to catalyze the synthesis of benzyl acetate using benzyl alcohol and acetyl-CoA as substrates, and the substrate benzyl alcohol has been shown to be synthesized from the reduction of benzaldehyde in plants 2,10 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that eugenol is the most important constituent of the characteristic floral scent of P . mume [6]. Eugenol, with the exotic smell of cloves, is among the volatile phenylpropanoid compounds derived from phenylalanine [7].…”
Section: Introductionmentioning
confidence: 99%
“…Most interspecific hybrids between P . mume and other species of Prunus lack this fragrance [6, 14], in which eugenol is a principal component contributing to the floral scent among both emitted and endogenous compounds. To solve this breeding problem, we must understand the molecular mechanism of eugenol production.…”
Section: Introductionmentioning
confidence: 99%
“…mume (mei) from Rosaceae, is a famous ornamental and fruit tree blooming in early spring within January and February, and it is mainly cultivated in Yangtze valley that locates in the subtropical monsoon climate zone [12]. It emits recognizable and pleasant scents, making it distinguishable from other species in Prunus, such as P. sibirica, P. armeniaca, and P. persica [13]. It has been reported that the aromatic benzenoid, benzyl acetate, is the main component in its floral volatiles [14].…”
Section: Introductionmentioning
confidence: 99%